2018
DOI: 10.1038/s41598-018-22171-6
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalyzed chemoselective ring-opening polymerizations

Abstract: A novel metal-free and protecting-group-free synthesis method to prepare telechelic thiol-functionalized polyesters is developed by employing organocatalysis. A scope of Brønsted acids, including trifluoromethanesulfonic acid (1), HCl.Et2O (2), diphenyl phosphate (3), γ-resorcylic acid (4) and methanesulfonic acid (5), are evaluated to promote ring-opening polymerization of ε-caprolactone with unprotected 6-mercapto-1-hexanol as the multifunctional initiator. Among them, diphenyl phosphate (3) exhibits great c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…If the magnetic coupling in the ab plane was of ferromagnetic nature, then the magnetic contribution to the Bragg reflections would be comparable for the 004 and for the 002 reflection since for ferromagnetic modes in the ab plane (irreducible representations 3 and 4, see Table T1 and T2) the magnetic structure factor would be modulated with l according to the periodic form cos[lπ(z1+z2)]*cos[lπ(z1-z2)]. Our measurements i zero field ( Figure 2) show however that this is not the case, on the contrary at around T* the reflection 002 is much more intense than the 004 which is in fact vanishing, and this difference is well beyond the attenuation of the magnetic scattering by the magnetic form factor at these two close scattering vectors [20]. propagation vector k = (0,0,0), calculated with BasIreps.…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…If the magnetic coupling in the ab plane was of ferromagnetic nature, then the magnetic contribution to the Bragg reflections would be comparable for the 004 and for the 002 reflection since for ferromagnetic modes in the ab plane (irreducible representations 3 and 4, see Table T1 and T2) the magnetic structure factor would be modulated with l according to the periodic form cos[lπ(z1+z2)]*cos[lπ(z1-z2)]. Our measurements i zero field ( Figure 2) show however that this is not the case, on the contrary at around T* the reflection 002 is much more intense than the 004 which is in fact vanishing, and this difference is well beyond the attenuation of the magnetic scattering by the magnetic form factor at these two close scattering vectors [20]. propagation vector k = (0,0,0), calculated with BasIreps.…”
Section: Resultsmentioning
confidence: 66%
“…Given the diversity of the inner and outer ruthenium atoms, we can speculate that the different sites be responsible for the two observed transitions at TC=105 K and at T*=50K. In a recent report [20], neutron scattering experiments have been able to ascertain the presence of a magnetic signal in the ab plane about T*, based on the observation of additional intensity in the 002, 006 and 008 reflections. The hyphothesis of a ferromagnetic axis sligtly tilted in the ab-plane at around T* has been put forward to explain the occurrence of magnetism in the ab plane, however no explanation has been provided for the absence of the 004 reflection.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…For general sample systems where different elements are not separated in the beam propagation direction, the decoupling of low-spatial-frequency features would rely on choosing the proper imaging mechanisms available in the multi-modality measurement scheme that best represents the structural properties of the sample. For example, the smallangle-scattering signal can be used for distinguishing materials with similar texture and electron density (Liebi et al, 2015;Zhu et al, 2018), and the Bragg diffraction can select crystal grains with different orientations (Huang et al, 2015b;Yau et al, 2017). Meanwhile, recent algorithm development shows that combining multi-slice ptychography with tomography and exploiting the redundant measurements at different angles helps the decoupling of low-spatial-frequency features.…”
Section: Figurementioning
confidence: 99%
“…Terzopoulu et al [3] reported the ROP of CL using SO as a catalyst and initiator. Similarly, other novel initiators such as benzylalcohol [4,5], gelatin [6], lipase [7], mercaptohexanol [8], diethyleneglycol [9], bisphenolate ligand [10] and mPEG [11] were used for the ROP of CL. Due to the bio-degradability and bio-compatibility of PCL, it is used as a drug carrier material.…”
Section: Introductionmentioning
confidence: 99%